2022
DOI: 10.1186/s12889-022-12767-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the national and subnational completeness of death registration in Nepal

Abstract: Background Reliable and timely mortality data from a civil registration and vital statistics (CRVS) system are of crucial importance for generating evidence for policy and monitoring the progress towards national and global development goals. In Nepal, however, the death registration system is not used to produce mortality statistics, because it does not providing data on age at death and only reporting deaths by year of registration. This study assesses the completeness of death registration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…A sizeable sex difference in death registration could be attributed to a lower proportion of females employed in the formal sector; therefore, a lower incentive is associated with female death registration. 13,14 In addition, a global scenario showed that female has a longer life expectancy than male, and India is not an exception to this fact, which may mean that there is no one to register a wife’s death after the death of the husband in a single household. 15 A higher proportion of accidental deaths among males (which are usually the subject of a police investigation) may lead to higher odds of death registration among males.…”
Section: Discussionmentioning
confidence: 99%
“…A sizeable sex difference in death registration could be attributed to a lower proportion of females employed in the formal sector; therefore, a lower incentive is associated with female death registration. 13,14 In addition, a global scenario showed that female has a longer life expectancy than male, and India is not an exception to this fact, which may mean that there is no one to register a wife’s death after the death of the husband in a single household. 15 A higher proportion of accidental deaths among males (which are usually the subject of a police investigation) may lead to higher odds of death registration among males.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted to assess the quality and completeness of death registration data found that the completeness of the paper-based death registration system (i.e. offline data) is 69% at the national level, being below 50% in recent years in Madhesh and Karnali [ 13 ]. The recently introduced online death registration system still only operates in a minority of districts throughout the country, and so has completeness of just 32% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…offline data) is 69% at the national level, being below 50% in recent years in Madhesh and Karnali [ 13 ]. The recently introduced online death registration system still only operates in a minority of districts throughout the country, and so has completeness of just 32% [ 13 ]. Further, a limitation of the offline registration data for the production of mortality indicators is that it does not provide aggregated data by age at death.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations